Promoting charge transfer in hyperbranched, trisoctahedral-shaped core–shell Au@PdPt nanoparticles by facet-dependent construction of transition layers as high performance electrocatalysts. Issue 35 (29th August 2017) - Song, Yahui; Bi, Cuixia; Wu, Chenshuo; He, Hongpeng; Huang, Lihui; Wang, Dayang; Xia, Haibing
Abstract : This is the first case of promoting charge transfer by facet-dependent construction of a transition layer between the core and the shell. Abstract : In this work, we report the production of hyperbranched, trisoctahedral-shaped core–shell Au@PdPt nanoparticles (HTCS Au@PdPt NPs) by facet-dependent growth of transition Pd layers and uniform PdPt alloy shells, respectively, by two batches of addition of the reducing agent, ascorbic acid (AA) solution, on preformed trisoctahedral (TOH) Au cores enclosed by {331} facets. It is found that the thickness and composition of the PdPt alloy shell of HTCS Au@PdPt NPs can be accurately controlled by varying the amount of the Pd and Pt precursors. Moreover, the ultrasmall PdPt branches (3.5 nm × 9.2 nm) on the TOH Au cores can lead to a significantly increased electrochemically active surface area (up to 55.4 m 2 gPt −1 ). Taking electrooxidation of methanol and formic acid by Au@PdPt catalysts as an example, three types of Au cores enclosed with different facets were selected to investigate the effect of the resulting transition Pd layer on the performance of CS NP-based catalysts with similar structures. By comparison of their electrocatalytic performance, the enhanced electrocatalytic performance of the HTCS Au100 @Pd20 Pt20 NPs can be mainly attributed to improved charge transfer between the well-defined TOH Au cores and the highly crystalline PdPt alloy shells besides the unique dendritic PdPt alloyed shell and core–shell structure. The as-prepared HTCS Au100 @Pd20 Pt20 NPs have excellent electrocatalytic performances in electro-oxidation of methanol (0.64 A mgPt −1 ) and formic acid (0.77 A mgPt −1 ), which are significantly higher than those of commercial Pt black (0.12 A mgPt −1 for both of methanol and formic acid) and other Au@PdPt NPs with Au cores enclosed with different facets. In addition, HTCS Au100 @Pd20 Pt20 NPs also exhibit the best durability among them possibly due to their superior anti-CO poisoning capability.